CHARACTERISTICS OF THE POETRY OF BYRON AND LERMONTOV AND ITS INFLUENCE ON THE POETRY OF OTHER POETS - Ruzibayeva Aziza Kahramanovna (Western European Studies, 2024)
This article examines the defining characteristics of the poetry of Lord Byron, and Mikhail Lermontov, emphasizing their unique contributions to the Romantic literary tradition. It identifies key themes such as the exploration of the self, the tension between personal freedom and societal constraints, and the deep connection to nature. The article further investigates their stylistic innovations, including the use of vivid imagery and unconventional rhyme schemes, which have influenced subsequent generations of poets. By analyzing the impact of Byron and Lermontov on other notable writers, the article highlights how their works continue to resonate in contemporary literature, shaping poetic expressions of individuality, rebellion, and the human experience
Keywords: Byron; Lermontov; Romantic poetry; individualism